Pengaruh Model Pembelajaran Inquiry Terhadap Kepercayaan Diri Pendidikan Jasmani - Anasa Firman Maliki; Bambang Ismaya; Resty Gustiawati (Peneliti.net, 2021)
The purpose of making this thesis is to determine the effect of the inquiry learning model on self-confidence in physical education. To answer the formulation of the research problem that has been formulated, the author uses a quantitative approach with experimental methods. This research was conducted at SMA Negeri 1 Tegalwaru by taking a sample of 30 people with 15 samples in the experimental group and 15 samples in the control group. There are three stages in this research, namely: pre-test or initial test, treatment or treatment, and post-test or final test. The pre-test was conducted on 15 samples to determine the results of inquiry learning on students' self-confidence before receiving treatment. The experimental design in this study was In this research design, there were two groups, each of which was randomly selected (R). The first group was given treatment (X) and the other group was not. Then the researchers conducted a post-test on 15 samples. After being treated, the research was then processed using the T-test formula and compared with the T-table. The results of the study show that the inquiry learning model has an influence on the lower self-confidence of the students of class X MIPA 2 SMA Negeri 1 Tegalwaru with the results of the T-test calculation of 0.012 and compared with the T-table of 0.05. It can be concluded from this research that there is an influence in doing learning so that students can do learning more independently and confidently in doing learning.